2018
DOI: 10.29121/granthaalayah.v6.i2.2018.1578
|View full text |Cite
|
Sign up to set email alerts
|

Research Efficiency Optical Transport Networks With Use Transferring and Reception Optoelectronics Module

Abstract: The analyses qualities functioning optical transport communication networks on the basis technology spectral divisions of the channels using transferring and reception optoelectronics of the module. On a basis research the method improvement indicators fiber-optical systems transfer information is offered and key parameters efficiency and a noise stability optical transport networks are defined.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 3 publications
0
3
0
Order By: Relevance
“…The main types attenuation in fiber optic cables used on FOCL, which determine the main types fiber loss [6,7,8,11] and are divided into four groups: a) Own losses; b) Cable loss; c) Absorption losses; d) Losses in scattering.…”
Section: Estimation Attenuation Parameters For Focl In the Transmissi...mentioning
confidence: 99%
See 2 more Smart Citations
“…The main types attenuation in fiber optic cables used on FOCL, which determine the main types fiber loss [6,7,8,11] and are divided into four groups: a) Own losses; b) Cable loss; c) Absorption losses; d) Losses in scattering.…”
Section: Estimation Attenuation Parameters For Focl In the Transmissi...mentioning
confidence: 99%
“…Based on the studies carried out, it is established [3,8] that for the estimation of kilometric damping parameters there are certain points in the FOCL where the main losses in the FOC arise. It was found that the main losses arise [4,6,9,10,11]:…”
Section: Estimation Attenuation Parameters For Focl In the Transmissi...mentioning
confidence: 99%
See 1 more Smart Citation